A rhesus monkey model for sexual transmission of a papillomavirus isolated from a squamous cell carcinoma. - Ostrow, R S (1990)
Recently we molecularly cloned and characterized a papillomavirus from a lymph node metastasis of a primary penile carcinoma found in a rhesus monkey; this virus species, rhesus papillomavirus type 1 (RhPV-1), is similar to oncogenic human papillomaviruses (HPVs), such as HPV-16 or HPV-18, in that the RhPV-1 DNA was found to be integrated in the tumor cell DNA. To compare the sexual transmission and oncogenic nature of RhPV-1 with these HPVs, we undertook an extensive retrospective study of a group of rhesus monkeys whose sexual mating and offspring histories were known. These animals had mated directly with the index male mentioned above or were secondarily exposed to this virus through intermediate sexual partners. This study combines cytological, histopathological, and several complementary hybridization and DNA amplification techniques on multiple tissue samples to demonstrate the sexually transmitted nature of RhPV-1. The oncogenic potential of RhPV-1 is suggested in several of the infected animals by the presence of various degrees of neoplasia including squamous cell cancer of the cervix.